2008
DOI: 10.19173/irrodl.v9i2.461
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Strategies in Teaching Engineering at a Distance: Faculty perspective

Abstract: This paper presents research on a convenience sample of the Open University of Sri Lanka's engineering faculty. Examined in this research are faculty's opinions on the instructional strategies they use to teach engineering courses at a distance. First, this paper details the pedagogical strategies used by the faculty, which is then followed by an overview of faculty's opinions on the strengths and weaknesses of engineering courses offered by the Open University of Sri Lanka. Recommendations are given to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…Les différentes modalités de cours sont considérées dans les analyses. À notre connaissance, les recherches internationales et nord-américaines réalisées au postsecondaire poursuivant cet objectif sont très rares, Lakhal et Bazinet (2015) cités plus haut en ont recensé quinze en tout : Ariadurai et Manohanthan (2008), Bocchi, Eastman et Swift (2004), Dinov, Sanchez et Christou (2008), Doherty (2006), Fey, Emery et Flora (2008, Hachey et al (2014), Ibrahim, Rwegasira et Taher (2007), Johnson et Galy (2013), Joo, Joung et Sim (2011, Kluwin et Noretsky (2005), Müller (2008), Ojokheta (2010), Price et Kadi-Hanifi (2011), Sutton et Nora (2008) et Xenos, Pierrakeas et Pintelas (2002. Les recherches québécoises poursuivant cet objectif sont, à notre connaissance, inexistantes.…”
Section: Introductionunclassified
“…Les différentes modalités de cours sont considérées dans les analyses. À notre connaissance, les recherches internationales et nord-américaines réalisées au postsecondaire poursuivant cet objectif sont très rares, Lakhal et Bazinet (2015) cités plus haut en ont recensé quinze en tout : Ariadurai et Manohanthan (2008), Bocchi, Eastman et Swift (2004), Dinov, Sanchez et Christou (2008), Doherty (2006), Fey, Emery et Flora (2008, Hachey et al (2014), Ibrahim, Rwegasira et Taher (2007), Johnson et Galy (2013), Joo, Joung et Sim (2011, Kluwin et Noretsky (2005), Müller (2008), Ojokheta (2010), Price et Kadi-Hanifi (2011), Sutton et Nora (2008) et Xenos, Pierrakeas et Pintelas (2002. Les recherches québécoises poursuivant cet objectif sont, à notre connaissance, inexistantes.…”
Section: Introductionunclassified
“…They clearly show the gap between enrollment and passing out of students (Statistical Handbook -2013, 2014). There will be many reasons for this situation (Ariadurai & Manohanthan, 2008;De Zoysa, Munasinghe, Seneviratne, & Mukunthan, 2011;Ismail, August 1997;Munro, 1987;Lekamge, Ranawake, Gunaratne, & Jayananda, 1999;Tinto, 2006Tinto, -2007.…”
Section: Problem Statementmentioning
confidence: 99%
“…Given these differences from traditional teaching methods, it seems reasonable to question the effectiveness of distance education methods. However, a number of studies have demonstrated that distance and online delivery methods are at least as or more effective than face-to-face methods in terms of student outcomes 7,8 .…”
Section: Review Of Literaturementioning
confidence: 99%